Brain organoids and organoid intelligence from ethical, legal, and social points of view - Hartung, Thomas; Morales Pantoja, Itzy E.; Smirnova, Lena (Frontiers in Artificial Intelligence, 2024)
Human brain organoids, aka cerebral organoids or earlier "mini-brains", are 3D cellular models that recapitulate aspects of the developing human brain. They show tremendous promise for advancing our understanding of neurodevelopment and neurological disorders. However, the unprecedented ability to model human brain development and funcBon in vitro also raises complex ethical, legal, and social challenges. Organoid Intelligence (OI) describes the ongoing movement to combine such organoids with ArBficial Intelligence to establish basic forms of memory and learning. This arBcle discusses key issues regarding the scienBfic status and prospects of brain organoids and OI, conceptualizaBons of consciousness and the mind-brain relaBonship, ethical and legal dimensions including moral status, human-animal chimeras, informed consent, and governance maWers such as oversight and regulaBon. A balanced framework is needed to allow vital research while addressing public percepBons and ethical concerns. Interdisciplinary perspecBves and proacBve engagement among scienBsts, ethicists, policymakers, and the public can enable responsible translaBonal pathways for organoid technology. A thoughXul, proacBve governance framework might be needed to ensure ethically responsible progress in this promising field.